Development of nowcasting technique and evaluation of convective indices for thunderstorm prediction in Gangetic West Bengal (India) using Doppler Weather Radar and upper air data (MAUSAM, 2012)
Thunderstorm and hailstorm are well known short term severe weather phenomena which sometimes turn in to natural hazard especially in Gangetic West Bengal region of India. Large vertical extent of the cumulonimbus cloud, very high reflectivity, squally wind speed sometimes exceeding 100 km/h and heavy rainfall are the main features of these thunderstorms during pre-monsoon period in this region. A study of 70 thunderstorms has been carried out during the pre-monsoon season (March-May) of the year 2005 around Kolkata (22.5° N, 88.5° E) using Doppler Weather Radar and Upper air data. Standard convective indices like CAPE, CINE, LI, BRN and VGP have been evaluated and analyzed statistically. As no definite thresholds of the convective indices are available for thunderstorm prediction in this region, an attempt has been made to find threshold of these indices for possible occurrences of thunderstorms in Gangetic West Bengal region after the analysis of the thunderstorms during year 2005. The validity of these convective indices has been checked with 34 occurrences of thunderstorms during 2006-2007 recorded by Doppler Weather Radar Kolkata. The study reveals that nowcasting of thunderstorms may be done at least 2-3 hrs in advance witha fair degree of accuracy using Doppler radar products only. However, the lead time of nowcasting may be further improved if the convective indices are also analyzed and used in addition to the DWR data. A simple technique has been suggested by the authors for better prediction of thunderstorms at least three to four hours in advance.